Analysis of The Effect of Leptin, AMPK, Adiponectin, and NPY Markers on Changes in Body Weight of Childhood Epileptic Using Valproic Acid Monotherapy - Wardah Rahmatul Islamiyah (EManuscript Technologies, 2023)
Abstract: Introduction: Epilepsy is a neurological disorder that occurs due to abnormal neurons in the brain and an imbalance between excitation and inhibition in the central nervous system. The first line of OAE in children is VPA (Valproate Acid). However, long-term use can cause weight gain with a frequency of 10-70%. The underlying mechanism of weight gain in patients remains unclear. Purpose: This study aimed to analyze the relationship between levels of biomarkers AMPK, NPY, Leptin, and Adiponectin on changes in body weight in patients with epileptic seizures using VPA monotherapy. Method: This study is an observational cohort design. Data collection in April-June 2019. Inclusion criteria were children aged 2-10 years who used VPA requirement less than two years, not taking any drugs that affect body weight, not diagnose systemic lupus, nephrotic syndrome, and diabetes mellitus. Bodyweight and all biomarkers measurement on subjects who came to the clinic at the time of study and at least after one month of taking VPA. A total of 17 subjects participated in this study. Result: The results of the statistical multivariate analysis test of VPA dosage on changes in body weight and biomarker levels found that Leptin, AMPK, Adiponectin did not significantly increase in body weight (p>0.05), but NPY significant increase in body weight (p<0.05). Conclusion: NPY is the most potent for appetite enhancing, preferential effect on carbohydrate intake, weight regulation, energy storage, and expenditure. Increase production of NPY, there is an increase in energy intake and then increases fat storage and body weight.